2024
DOI: 10.1038/s41398-024-02773-7
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic analysis in mice following a single dose of ibogaine identifies new potential therapeutic targets

Judit Biosca-Brull,
Genis Ona,
Lineth Alarcón-Franco
et al.

Abstract: Ibogaine (IBO) is an atypical psychedelic with a complex mechanism of action. To date, the mechanisms that may underlie its anti-addictive effects are still not defined. This study aims to identify changes in gene expression induced by a single oral dose of IBO in the cortex of mice by means of a transcriptomic analysis for the first time. Our results showed significant alterations in gene expression in mouse frontal cortex samples 4 h after a single oral dose of IBO. Specifically, genes involved in hormonal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Furthermore, female sex is among the additional risk factors for drug-induced TdP arrhythmias that should be considered before the use of ibogaine [ 6 ]. Previous results have shown that the bioavailability of ibogaine and its principal in vivo metabolite, noribogaine, is two to three times higher in female rats than in male rats [ 9 , 10 ] and that ibogaine has sex-specific effects on the central nervous system [ 11 , 12 , 13 ], liver, and kidneys, with ibogaine-induced pathological changes being more pronounced in female rats [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, female sex is among the additional risk factors for drug-induced TdP arrhythmias that should be considered before the use of ibogaine [ 6 ]. Previous results have shown that the bioavailability of ibogaine and its principal in vivo metabolite, noribogaine, is two to three times higher in female rats than in male rats [ 9 , 10 ] and that ibogaine has sex-specific effects on the central nervous system [ 11 , 12 , 13 ], liver, and kidneys, with ibogaine-induced pathological changes being more pronounced in female rats [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%